The Differences Between 'Uken' and 'Toa' in the Gayo Dialect - Evi Lestaria (EDUJ : English Education Journal, 2024)
This paper examines the distinctions between the terms 'uken' and 'toa' within the Gayo dialect, spoken in the Gayo Highlands of Aceh, Indonesia. Both terms hold significant semantic and functional roles in the Gayo language, yet they differ markedly in usage and context. 'Uken' is typically employed in formal or traditional contexts, often carrying connotations of respect or authority. In contrast, 'toa' is more frequently used in informal or everyday interactions, reflecting different aspects of social hierarchy and communication style. Through a comparative analysis of these terms, this study aims to elucidate their respective meanings, cultural significance, and the roles they play in shaping social dynamics within the Gayo-speaking community. By understanding these differences, we gain insights into the intricate ways language reflects and influences social relationships in this unique cultural setting.